The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1159/000056002
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors in Children with Severe Diffuse Brain Injuries: A Study of 74 Patients

Abstract: Severe diffuse brain injury in children has a devastating influence on their physical and psychological development. This retrospective study was undertaken to analyse the factors that influence outcome in children with such injuries. The short-term outcomes (Glasgow outcome score) of 74 children (age ≤15 years) with severe diffuse brain injury and no focal operable mass lesions on CT scan, admitted between 1992 and 1998 at the National Institute of Mental Health and Neurosciences were analysed. The prognostic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(20 citation statements)
references
References 24 publications
0
19
0
1
Order By: Relevance
“…Once brain damage is suspected, several neurological sequelae have been described, with no clear trend towards an specific brain injury. 31,33,34 Follow-up of these patients, has shown that partial to complete recovery of these findings is registered in the longterm evolution of many patients. Pediatric brain damage, when not extreme, still holds some margin of recuperation, and 1 year after cardiac arrest, even the majority of those who had worsen their neurological scales, showed some improvement.…”
Section: Discussionmentioning
confidence: 91%
“…Once brain damage is suspected, several neurological sequelae have been described, with no clear trend towards an specific brain injury. 31,33,34 Follow-up of these patients, has shown that partial to complete recovery of these findings is registered in the longterm evolution of many patients. Pediatric brain damage, when not extreme, still holds some margin of recuperation, and 1 year after cardiac arrest, even the majority of those who had worsen their neurological scales, showed some improvement.…”
Section: Discussionmentioning
confidence: 91%
“…Along these lines, Hirsch and colleagues [13] found a relation between the initial HCT and prognosis in a study that included scans from 248 children, and Pillai and colleagues [14] showed that oculocephalic reflex and GCS were the most important variables for predicting outcome. A recent study performed at a Canadian hospital [15] that included 83 children with moderate (GCS Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In post-traumatic patients these disorders may vary according to several factors such as different recovery stages and gender [8][9][10][11][12], but also have different features depending on patient's age [13]. These children mainly show attention deficits, hyperkinesia and hyperactivity, irritability, aggressiveness and opposition behaviour [14,15].…”
Section: Introductionmentioning
confidence: 99%